Structural and Catalytic Roles of Metal Ions in RNA - Sigel, Astrid; Sigel, Helmut; Sigel, Roland K. O. (Metal Ions in Life Sciences ;, 2015)
Metal Ions in Life Sciences links coordination chemistry and biochemistry in their widest sense and thus increases our understanding of the relationship between the chemistry of metals and life processes; in fact, it is an old wisdom that metals are indispensable for life. The series reflects the interdisciplinary nature of Biological Inorganic Chemistry and coordinates the efforts of scientists in numerous interconnecting research fields.